Dp71 Expression in Human Glioblastoma - Ruggieri, Simona (Int J Mol Sci, 2019)
Background: Dp71 is the most abundant dystrophin (DMD) gene product in the nervous system. Mutation in the Dp71 coding region is associated with cognitive disturbances in Duchenne muscular dystrophy (DMD) patients, but the function of dystrophin Dp71 in tumor progression remains to be established. This study investigated Dp71 expression in glioblastoma, the most common and aggressive primary tumor of the central nervous system (CNS). Methods: Dp71 expression was analyzed by immunofluorescence, immunohistochemistry, RT-PCR, and immunoblotting in glioblastoma cell lines and cells isolated from human glioblastoma multiforme (GBM) bioptic specimens. Results: Dp71 isoform was expressed in normal human astrocytes (NHA) cell lines and decreased in glioblastoma cell lines and cells isolated from human glioblastoma multiforme bioptic specimens. Moreover, Dp71 was localized in the nucleus in normal cells, while it was localized into the cytoplasm of glioblastoma cells organized in clusters. We have shown, by double labeling, that Dp71 colocalizes with lamin B in normal astrocytes cells, confirming the roles of Dp71 and lamin B in maintaining nuclear architecture. Finally, we demonstrated that decreased Dp71 protein in cells isolated from human bioptic specimens was inversely correlated with the Ki-67 tumor proliferative index. Conclusion: A decreased Dp71 expression is associated with cancer proliferation and poor prognosis in glioblastoma.